C-arm CT-guided renal arterial embolisation followed by radiofrequency ablation for treatment of patients with unresectable renal cell carcinoma. Issue 1 (January 2016) - Duan, X.-H.; Li, Y.-S.; Han, X.-W.; Wang, Y.-L.; Jiao, D.-C.; Li, T.-F.; Chen, P.-F.; Fang, Y.
Abstract : Aim: To explore the value of using flat detector (FD) equipped angiographic C-arm CT (CACT) systems in treating unresectable renal cell carcinoma (RCC) by selective renal arterial embolisation (RAE) followed by radiofrequency ablation (RFA) (RAE-RFA). Materials and methods: A total of 28 patients who were not candidates for surgery were enrolled. The average size of tumours was 6.7±2.2 cm (range 4.1–9.6 cm). Twenty-eight tumours were treated with CACT-guided RFA, 5–7 days after CACT-guided RAE. Results: CACT-guided RAE-RFA was technically successful in all patients. Tumour enhancement disappeared after a single RAE-RFA session in 20 patients, after two RAE-RFA sessions in four patients and after three RAE-RFA sessions in the other four patients. One patient died of lung metastasis and haematuria 13 months after RAE-RFA, and another patient died of pulmonary heart disease 23 months after repeat RAE-RFA. In the 26 living patients, tumours remained controlled during a mean follow-up period of 27 months and showed significant reduction in tumour size (6.7±2.2 cm to 3.9±1.7 cm, p <0.01). There were no significant changes in creatinine levels or urea nitrogen concentrations before and after the last RAE-RFA ( p >0.05). There were no serious complications during and after the procedure. Conclusion: CACT-guided RAE followed by RFA appears to be a safe and effective technique for treating patients with inoperable RCC. Highlights: Selective RAE combined with RFA (RAE-RFA) is used to treat unresectable RCC. We assessed the C-arm CT (CACT) based needle guidance system to perform RAE-RFA. Tumors were controlled and reduced in size following CACT-guided RAE-RFA. No significant changes in renal function occurred post-CACT-guided RAE-RFA. CACT-guided RAE-RFA for treating RCC appears to be a safe and effective technique.